PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEAD TOGETHER (NHT) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 140 PEKANBARU - Agustina Agustina; Hendri Marhadi; Jesi Alexander Alim (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : The research carried out base on the lowly of the result of math subject in grade 4th SDN 88 Pekanbaru which is about 65.3 within minimal completeness criterion stated is 74. Among 30student, there was only 13 students were able to achieve the score of minimal completeness criterion stated. The purpose of this research is to improve student’s achievemet on math of the five graders in SDn 88 Pekanbaru with the application of Numbered Head Together. This research was classroom action research consisting 2 cycles within 4 procedures : planning, doing, observing, and reflecting and each cycle consist of three meeting. Instruments on this research are syllabus, lesson plan, and student work sheet. Instrument for collecting data are observation sheet and test. Data which was collected were learning outcomes and teacher’s activities during lessons. After implementation of contextual teaching and learning model it was abtained student’s outcomes in UH I within average 65.03 basic score 8.91%. The average score form UH II was 70,83 (improved 50 %). Teachers activities results in the first meeting of the first cycle was 70% (good category), and then 78% (good category) for the second meeting in cycle I. Meanwhile in the first meeting of the second cycle was 85% (very good category) and then 97% (very good category) for second meeting in cycle II. Students activity in the first meeting of the cycle I was 70% (fair category), 78% (good category) for the second meeting in the cycle I. And then in the first meeting of the second cycle was930% (veri good category), 95% (very good category) for the second meeting in cycle II. Based on the result it can be concluded that implementation of numbered head together(NHT) model can math in four graders at SDN 88 PekanbaruKeywords : Numbered Head Together, Students Achievement the Result Of math Studies.